If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1c + 1a = 3 Reorder the terms: 1a + 1c = 3 Solving 1a + 1c = 3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1c' to each side of the equation. 1a + 1c + -1c = 3 + -1c Combine like terms: 1c + -1c = 0 1a + 0 = 3 + -1c 1a = 3 + -1c Divide each side by '1'. a = 3 + -1c Simplifying a = 3 + -1c
| (28b-6)-9(3b+2)=-6 | | 30v-60=120 | | 2p^2-20p+48= | | X^2+9xy+14y^2= | | 30v+60=90 | | x^3-2x^2+2x=400 | | 8x+3+5x+8=12x+4 | | 8x+3+5x+8=12+4 | | 2x^4-11x^3+17x^2=0 | | 20c+40=100 | | 3.3x-3=2.3x | | 8x+4=5x+16 | | 4a^2+6a-18=0 | | 2+y=13-3(y+1) | | -15=2x-5 | | 2e+4=6 | | (a+3b)(2a-ab)= | | 35y^2-4y-15=0 | | -(4x-6)+3(2x-4)+3=0 | | 7m+14=21 | | 4x-(4*3x)=4 | | 5n+4=20 | | 10(10+x)=20 | | n^6=90 | | 7(y-5)=-3(4+y) | | (x+4)(x-17)=x | | 16y+32=48 | | 34-2(4+5)= | | 5x-7=2x-6 | | 7x+14=28 | | 6y+18=24 | | 12x+1=91-6x |